2013
DOI: 10.1016/j.neuroscience.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mRNA and protein expression for 12 GABAA receptor subunits in the mouse brain

Abstract: Graphical abstractHighlights► The distribution of GABAA receptor subunits is highly heterogeneous. ► The distribution of mRNAs corresponds to that of proteins. ► The distribution in the mouse correlates largely to that in rats although there are distinct differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
226
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(248 citation statements)
references
References 42 publications
19
226
1
2
Order By: Relevance
“…It has been shown that the D1-and D2-expressing MSNs have opposite effects on behavioral sensitization to and the development of conditioned place preference to cocaine (Lobo et al, 2010). Dense staining in earlier studies (Fritschy and Mohler 1995;Hörtnagl et al, 2013;Pirker et al, 2000) and our immunohistochemical analysis of the virally-infected cells in wild-type mice suggest that a large population of MSNs in the NAc expresses a2GABA A Rs. D2-positive MSNs project to the VP (Smith et al, 2013), which in turn sends GABAergic projections onto the VTA (Kalivas et al, 1993), at least partially onto GABAergic interneurons (Kaufling et al, 2009).…”
Section: Discussionmentioning
confidence: 53%
“…It has been shown that the D1-and D2-expressing MSNs have opposite effects on behavioral sensitization to and the development of conditioned place preference to cocaine (Lobo et al, 2010). Dense staining in earlier studies (Fritschy and Mohler 1995;Hörtnagl et al, 2013;Pirker et al, 2000) and our immunohistochemical analysis of the virally-infected cells in wild-type mice suggest that a large population of MSNs in the NAc expresses a2GABA A Rs. D2-positive MSNs project to the VP (Smith et al, 2013), which in turn sends GABAergic projections onto the VTA (Kalivas et al, 1993), at least partially onto GABAergic interneurons (Kaufling et al, 2009).…”
Section: Discussionmentioning
confidence: 53%
“…In some cells expression of more than eight different isoforms has been demonstrated [5]. Throughout the CNS some subunits are broadly expressed, while others exhibit more restricted expression profile [17,18]. For example, the most abundant α1 subunit is expressed almost ubiquitously in the brain, α5 is highly expressed in the hippocampus, α6 subunit is expressed only in granule cells of the cerebellum, while ρ-subunits, the major molecular components of the formerly called GABAC receptors, are expressed mainly in the retina [19][20][21][22].…”
Section: Gabaa Receptors and Their Subunitsmentioning
confidence: 99%
“…Recent immunohistochemical and electrophysiological data demonstrated the expression of ␣1-and ␦-subunits in the CeAm in mice (Herman et al 2013). Because there is evidence that the expression of the ␣1-subunit is much lower in CeAl compared with CeAm (Hortnagl et al 2013) and because the GABA A R ␦-subunit is the main target of neurosteroid action, we focused on this subunit.…”
Section: Tonic Inhibitory Transmission Is Present In Cea Neuronsmentioning
confidence: 99%